2004
DOI: 10.1007/s11325-004-0201-5
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Apnea Avoidance Pillow Effects on Obstructive Sleep Apnea Syndrome and Snoring

Abstract: A uniquely designed pillow (SONA Pillow) is effective in reducing the number of events in patients with mild to moderate obstructive sleep apnea. Using this pillow also reduces snoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 8 publications
(7 reference statements)
0
24
0
Order By: Relevance
“…Accordingly, patients with a clear improvement of the AHI with positional therapy tended to be younger, to have a lower AHI and to be less obese [42,52,53]. It is not possible to extract from the data whether AHI, age or obesity is the best predictor of treatment success.…”
Section: Overview Of the Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, patients with a clear improvement of the AHI with positional therapy tended to be younger, to have a lower AHI and to be less obese [42,52,53]. It is not possible to extract from the data whether AHI, age or obesity is the best predictor of treatment success.…”
Section: Overview Of the Evidencementioning
confidence: 99%
“…Different devices such as tennis balls, vests, positional alarms, verbal instruction and pillows are used to avoid the supine position [53][54][55][56][57][58]. There are no data comparing the different devices, with the exception that verbal instructions seem to be less effective than a positional alarm [42,59].…”
Section: Overview Of the Evidencementioning
confidence: 99%
“…One study described one night's use of a specifically designed pillow to avoid the supine position in 22 patients, nine of whom were older than 65 years [102]. This study compared nocturnal respiratory parameters between a baseline night and a night with the supine-avoiding pillow in patients with mild-to-severe OSA.…”
Section: Positional Therapymentioning
confidence: 99%
“…It can occur independently of BMI, age, upper airway anatomy, or lung function [26,27]. However, the patients who respond to positional therapy tend to be younger, have a milder form of OSA with a lower BMI [15,24,25,28,29]. Positional therapy refers to the use of postural changes during sleep to improve OSA.…”
Section: Positional Therapymentioning
confidence: 99%
“…However, studies failed to show any superiority from one to another except for positional alarm which appears to be more effective than verbal instructions [15,30]. Positional therapy can result in moderate reductions of AHI [28,29,[31][32][33][34], but is overall inferior to CPAP therapy [35] and its long-term compliance has been poor [33]. In contrast, a recent study [36] showed that newer positional devices could significantly reduce the apnea/hypopnea index (AHI) from a baseline of 26/h to 6/h, with improvement in oxygenation and an objective compliance averaging 73.7%.…”
Section: Positional Therapymentioning
confidence: 99%